MODELLING CONSUMER BEHAVIOUR IN THRIFTING: A SYSTEMATIC ANALYSIS OF SUSTAINABLE APPAREL PRACTICES IN THE INDIAN CONTEXT - Mariya Ali; Dr. Sadaf Siraj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The global fashion industry is increasingly criticised for its environmental impact, resulting in a surge in alternative consumption habits like thrifting. Thrifting adheres to circular fashion principles by prolonging the lifespan of clothing, thereby diminishing waste and resource use. Cultural characteristics of India, such as resource conservation and frugality, facilitate the adoption of thrifting. Nonetheless, studies of this issue within the Indian setting are scarce. This conceptual study analyses thrifting as a sustainable behaviour in India, connecting it to sustainable clothing consumption. The study provides a paradigm that integrates the Theory of Planned Behaviour (TPB) with value-based consumption theories to address the cultural, economic, and environmental determinants of consumer behaviour. This study offers a refined comprehension of the role of thrifting in promoting sustainable clothing practices in India, addressing deficiencies in previous studies.